Endovascular treatment for blood blister ⁃ like aneurysms of internal carotid artery and systematic literature review - ZHOU Lei; WANG Zhong; YANG Guo‐jun; DONG Shi‐biao; LI Nan; ZHU Wei‐wei (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To explore endovascular treatment for patients with blood blister ⁃ like aneurysms (BBA) of the internal carotid artery (ICA). Methods and Results A retrospective analysis of the clinical data of 25 patients with BBA of ICA admitted to The First Affiliated Hospital of Soochow University from January 2018 to January 2022 were conducted. All of them accepted endovascular treatment: 17 cases were treated with single⁃stent⁃assisted embolization, including 14 cases using Lvis stents and 3 cases using Enterprise stents; 4 cases were treated with double⁃stent⁃assisted embolization, all using Lvis stents; one case was treated with overlapping stent implantation, including 2 Lvis stents and one Enterprise stent; one case was treated with balloon ⁃assisted embolization, and 2 cases were treated with Tubridge flow diverter. No aneurysm rupture occurred during the surgery. One patient had intra ⁃ stent thrombosis during the procedure, while other 24 patients showed smooth blood flow on postoperative immediate DSA. The Raymond classification showed that among the patients, there were 17 cases of grade Ⅰ occlusion, 3 cases of grade Ⅱ occlusion, and 5 cases of grade Ⅲ occlusion. Postoperative complications included cerebral infarction (2 cases), cerebral vasospasm due to subarachnoid hemorrhage (one case), and hydrocephalus (2 cases). Six patients had aneurysm recurrence postoperatively (3 cases using a single Enterprise stent, one case using 2 Lvis stents, one case using Tubridge flow diverter, and one case using a balloon ⁃ assisted embolization), among whom 5 patients underwent repeat stent ⁃ assisted embolization treatment. And one patient still had recurrence after treatment but achieved cure by adjusting antiplatelet therapy regimen; one patient recovered by adjusting antiplatelet therapy regimen. At 12 months after surgery, the modified Rankin Scale (mRS) scores were as follows: 0 in 15 cases, 1 in 6 cases, 2 in 3 cases, and 6 in one case. The disability rate was 12% (3/25), and the mortality rate was 4% (1/25). Conclusions The degree of immediate postoperative occlusion is crucial for preventing aneurysm recurrence postoperatively. For recurrent BBA of ICA, adjustment of antiplatelet therapy should be considered first.